Pemberdayaan Masyarakat Miskin Melalui Program Padat Karya Tunai Desa Dalam Perspektif Ekonomi Pembangunan Islam (Studi Kasus Desa Banua Lawas Kabupaten Kotabaru) - Hairullah, Fazry; Ansharullah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Empowerment of poor communities is an initiative from individuals or groups to improve the quality of life, both socially and economically. This research focuses on exploring efforts to empower poor communities through village cash-intensive programs, by analyzing the economic perspective of Islamic development in Banua Lawas Village, Kotabaru. This research method is field in nature with a descriptive approach, carried out in Banua Lawas Village, Kelumpang Hulu District, Kotabaru Regency, South Kalimantan. The informants consisted of 12 people, including 2 village officials and 10 village cash labor program workers. Data was collected through interviews and documentation. The research results show that the village cash-intensive program has succeeded in empowering poor communities according to the theory of Jim Ife and Frank Tesoriero. The village government acts as a facilitator, educator, representative and technology supporter to achieve the program's objectives. Empowerment of poor communities is in accordance with the concept of Islamic development economics by M. Umer Chapra, by fulfilling the principles of monotheism, rububiyah, khalifah, and takziyah, as well as achieving Islamic economic goals, including fulfilling basic needs, increasing human dignity, sustaining life, and advancing community spirituality. Keywords: Community Empowerment; Poor, Village Cash Labor Intensive; Qualitative; Islamic Economics Abstrak Pemberdayaan masyarakat miskin adalah inisiatif dari individu atau kelompok untuk meningkatkan kualitas kehidupan, baik secara sosial maupun ekonomi. Penelitian ini difokuskan pada eksplorasi upaya pemberdayaan masyarakat miskin melalui program padat karya tunai desa, dengan menganalisis perspektif ekonomi pembangunan Islam di Desa Banua Lawas, Kotabaru. Metode penelitian ini bersifat lapangan dengan pendekatan deskriptif kualitatif, dilaksanakan di Desa Banua Lawas, Kecamatan Kelumpang Hulu, Kabupaten Kotabaru, Kalimantan Selatan. Informan terdiri dari 12 orang, termasuk 2 aparatur desa dan 10 pekerja program padat karya tunai desa. Data dikumpulkan melalui wawancara dan dokumentasi. Hasil penelitian menunjukkan bahwa program padat karya tunai desa berhasil memberdayakan masyarakat miskin sesuai teori Jim Ife dan Frank Tesoriero. Pemerintah desa berperan sebagai fasilitator, edukator, representatif, dan pendukung teknologi untuk mencapai tujuan program tersebut. Pemberdayaan masyarakat miskin sesuai konsep ekonomi pembangunan Islam oleh M. Umer Chapra, dengan memenuhi prinsip tauhid, rububiyah, khalifah, dan takziyah, serta mencapai tujuan ekonomi Islam, termasuk pemenuhan kebutuhan dasar, peningkatan martabat manusia, keberlanjutan hidup, dan kemajuan spiritualitas masyarakat. Kata Kunci: Pemberdayaan Masyarakat;Miskin, Padat Karya Tunai Desa; Kualitatif; Ekonomi Islam